The Effect of the Covid 19 Pandemic on the Financial Performance of Companies in the Tourism Sector Listed on the Indonesia Stock Exchange - Basunanda, Arka Yogaswara; Setyorini, Haryati (Directorate of Academic Research and Community Services, 2022)
ABSTRACT The purpose of this research to analyze the effect of the covid 19 pandemic on the financial performance of companies in the tourism sector listed on the Indonesian stock exchange during 2019 to 2021. This type of research is explanatory. The population of this study are tourism sector companies listed on the Indonesia Stock Exchange from 2019 to 2021. The sample in this study are 12 tourism companies selected by purposive sampling. The data used is secondary data in the form of financial statements of tourism companies. The analytical tool in this study uses SPSS with the analysis technique of the sample paired t test. The results of this study indicate that the Return on Equity Variable there is no significant difference in tourism companies listed on the Indonesia Stock Exchange, the Operating Profit Margin Variable there is no significant difference in tourism companies listed on the Indonesia Stock Exchange, the Return on Assets variable has no significant difference in tourism companies listed on the Indonesia Stock Exchange, the Variable Current Ratio there is no significant difference in tourism companies listed on the Indonesia Stock Exchange, the Variable Debt to Equity Ratio there is no significant difference in the tourism companies listed on the Indonesia Stock Exchange, the Variable Size of the Company does not exist significant difference in tourism companies listed on the Indonesia Stock Exchange. Keywords : Covid 19 Pandemic, Financial Performance